Resistance, deportation and memory policies. Spanish in France (1940-1945) - Gaspar Celaya, Diego (Hispania Nova, 2019)
Between 1940 and 1945, more than 9,000 Spaniards were deported and interned in Nazi camps. For decades, Spanish society was deprived of the fate of its compatriots. However, when the Spanish deportation finally attracted the attention of professionals and the media, in the early 1990s, this resulted in the identification and study of the deported Spaniards, their life-itineraries and their experiences of internment. This article intends to contribute to expand our knowledge about Spanish deportation, through the analysis of the Spanish deported interned resisters (DIR) records conserved on French Defence archives, a novel source on Spanish deportation study that it will allow us to deepen on the relationship between the internment of Spaniards in Nazi camps and their participation in the Resistance in France.
Keywords: resistance; deportation; internment; Spanish refugees; CTE; Spanish exile; DIR